Optimization of Digital Marketing Strategies to Increase Revenue from The Tourism Sector in Kota Pari Village - Ritonga, Husni Muharram; Daulay, Muhammad Toyib; Erwansyah, Erwansyah; Mukti, Jihan Tri (Journal of Community Research and Service, 2023)
Kota Pari Village, PantaiCermin District, SerdangBedagai Regency, was the focus of this research because its residents saw a need to promote its tourist attractions online. The term "digital marketing" refers to the usage of digital tools by the majority of an organization's marketing team. To increase marketing and reach target markets via digital marketing, the tourism administrators in Kota Pari Village are the primary focus of this research. To do this, they will need to make use of information dissemination tools and online sales promotion, such as social media and websites, which are accessible to people all over the world. MaterialtobesubmittedtotheresearchThis is a digital marketing approach for the tourism industry to ensure a high volume of customers. In Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency, the findings indicated that both strategy (X1) and digital marketing (X2) had a favorable and significant influence on increasing visits to tourism areas. With the results of this study, businesses and tourists in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency can adapt to the changing times and provide for the needs of those who come to visit.